The Effect of Marketing Communications on Consumer Decisions in Using The XL Cellular Card In Banda Aceh: Consumer Motivation a Mediation Variable - Jamali; Jamil, Muhammad (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2021)
Modern marketing is not only oriented by developing good products, interesting rate members, and making them affordable for consumers, but the company has to build communication with the potential consumers in order to receive their aspirations and wills intended to fulfill and satisfy the consumers' need. This research is focused on the impact of marketing communication on the consumers' decision in using cellular card XL, through consumers' motivation. The goal of this study is to determine whether there is an indirect effect of marketing communication for consumer decisions through consumer motivation. The object of this study is the user's XL in Banda Aceh. The sampling method used in this study is the purposive sampling method, the method of sampling based on certain criteria. The analysis technique used is path analysis. The result of this study indicates that marketing communication directly has positive and significant effects on consumers' motivation, consumers' motivation has positive and significant effects on consumers' decisions, and marketing communication has positive and significant effects on consumers' decisions. Meanwhile, marketing communication indirectly has positive effects on consumers' decisions through consumers' motivation.